2019
DOI: 10.1111/jgh.14829
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability, tolerability, and safety of fecal microbiota transplantation in patients with active ulcerative colitis (AT&S Study)

Abstract: Background and Aim Fecal microbiota transplantation (FMT) targets gut microbiome dysbiosis and is an emerging therapy for ulcerative colitis (UC). Although initial results with FMT in patients with active UC are encouraging, data regarding its acceptability, tolerability, and safety are scant. Methods A retrospective analysis of patients with active UC (Mayo clinic score ≥ 4), who received multisession FMT (at weeks 0, 2, 6, 10, 14, 18, and 22) via colonoscopy between June 2016 and June 2018, was performed. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 20 publications
1
53
0
Order By: Relevance
“…The role of FMT in the treatment of pediatric UC is still debated, although the safety and tolerability of this clinical practice have already been assessed [ 16 , 17 , 28 ]. Recent reviews examined the current state of knowledge on FMT in IBD, and concluded that translational research on FMT is important in order to transfer its potential to real clinical management [ 15 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of FMT in the treatment of pediatric UC is still debated, although the safety and tolerability of this clinical practice have already been assessed [ 16 , 17 , 28 ]. Recent reviews examined the current state of knowledge on FMT in IBD, and concluded that translational research on FMT is important in order to transfer its potential to real clinical management [ 15 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The success of FMT for the treatment of Clostridium difficile infection has been proven [ 8 , 9 ]. However, several articles have already reported on FMT’s potential therapeutic use in GI and GI-related diseases, including IBD [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…15,39 In recent years, GM transplantation (GMT) has been considered to be a highly promising safe and effective treatment for a variety of diseases. 40,41 A growing number of studies indicate that GTM is a potential preventive and curative treatment for obesity and related metabolic diseases. [42][43][44] F I G U R E 5 AGMT induces BAT activity in HFD mice.…”
Section: Agmt Increases Intestinal Absorptive Surface and Reduces Imentioning
confidence: 99%
“…These should, however, not be attributed to co-incident COVID-19. Lastly, however, the isolation of the virus from fecal samples has implications for fecal microbiota transplants [45,46]. Although presently undocumented, COVID-19 might potentially spread during fecal microbiota transplants, and hence, it might be prudent to demonstrate negative viral RT-PCR multiple times in donor samples before accepting fecal samples for transplant.…”
Section: Introductionmentioning
confidence: 99%